The chemical, mechanical, and hydrological evolution of weathering granitoid. Issue 8 (8th August 2016) - Goodfellow, Bradley W.; Hilley, George E.; Webb, Samuel M.; Sklar, Leonard S.; Moon, Seulgi; Olson, Christopher A.
Abstract: Surprisingly few studies connect the chemical, mechanical, and hydrological evolution of rock as it weathers to saprolite and soil. We assess this coevolution in granodiorite from Monterey Peninsula, California, by measuring changes in bulk chemistry, mineralogy, volumetric strain, the oxidation state of Fe in biotite crystals, tensile strength, abrasion rate, connected porosity, and hydraulic conductivity in samples covering a range of weathering grades. We identify the oxidative dissolution of biotite as the key chemical reaction because of the volumetric expansion that accompanies formation of altered biotite and precipitation of ferrihydrite. We show how the associated accumulation of elastic strain produces an energy density that is sufficient to support rock fracturing over length scales equivalent to constituent crystals. The resulting intragranular and intergranular cracking profoundly reduces tensile strength and increases the abrasion rate, connected porosity, and hydraulic conductivity of the rock matrix. These changes increase the rate of plagioclase weathering, and ultimately the rock disintegrates into grus and clay. Major changes in rock properties can occur with only minor element leaching, and the threshold behavior of weathering that arises from the coevolution of chemical, hydrological, and mechanical properties may be difficult to capture using simplified weathering models that fail to incorporate these properties. Our results, which combine the mechanical and hydrological evolution of weathering rock with more common measurements of chemical changes, should help to more accurately model the effects of, and mechanical and hydrological feedbacks upon, chemical weathering of rock. Key Points: Chemical, mechanical, and hydrological evolution of weathering granite linked through Fe oxidation Profound alteration of rock mechanics and hydrology accompany slight chemical weathering The accumulation of strain at the crystal scale from oxidizing biotite fractures the rock matrix